Effects of resveratrol-loaded dendrimer nanomedicine on hepatocellular carcinoma cells - Qu, Jiao; Zhang, Yueqin; Song, Cong (Frontiers in Immunology, 2024)
Resveratrol (Res), a Chinese herbal extract, has demonstrated a remarkable and distinct antitumor effect, characterized by prolonged efficacy and minimal adverse reactions. However, the bioavailability of Res in animals is hindered by limited absorption rates. Therefore, it is crucial to enhance the tumor-targeting ability of resveratrol to optimize cancer treatment outcomes by improving its bioavailability. Herein, we attempt to employ a functionalized nanoparticle drug carrier system based on polyamine-amine (PAMAM) dendrimers for targeted delivery of resveratrol in hepatocellular carcinoma cancer treatment. Initially, galactose-modified fifth-generation (G5) PAMAM dendrimers (G5-Gal) were synthesized through coupling reactions, followed by the synthesis of glycosylated dendrimers incorporating resveratrol (G5(Res)-Gal) via physical encapsulation. The G5-Gal or G5(Res)-Gal complexes were characterized using 1H NMR spectroscopy, zeta and size analysis, and UV spectrophotometry. Additionally, Hepa1-6 mouse hepatoma cells were utilized as model cells to assess the targeting capability of G5-Gal toward hepatoma cells using flow cytometry. Finally, CCK-8 assay was employed to evaluate the impact of G5(Res)-Gal on normal liver cells as well as its cytotoxicity against different types of hepatoma cells. Furthermore, cell apoptosis experiments were conducted to further evaluate the effects of G5(Res)-Gal on Hepa1-6 cells. The aim of this project is to establish a solid theoretical framework and provide technical expertise to optimize the application of resveratrol and advance its delivery system.